Life Objectives as the Determinants of Happiness Among Muslims in Indonesia - Alfajri, Azriel; Kornitasari, Yenny (Islamic Economics and finance in Focus, 2025)
This research is motivated by allegations of life goals that also contribute to happiness. Non-competitive life goals—such as family goals, altruism, and religiosity—are thought to have a constructive influence on happiness, and competitive goals are detrimental. Using data from IFLS 5 and Muslims as subjects, this study aims to examine the suitability of previous research in the context of Muslims in Indonesia. The study utilized a quantitative descriptive approach with a binary logistic regression estimation model. The results revealed: (i) success goals measured by employment status had a negative and significant influence only on a sample of women; (ii) family goals have a positive and significant influence on Muslim happiness; (iii) altruism has a positive but insignificant influence on Muslim happiness; and (iv) religiosity has a positive and significant influence on Muslim happiness. These results could provide guidance for individual Muslims to discover the factors that increase their happiness, which ultimately contribute to economic development.